Spaceship Archeology: Methodological Experiments in NSF Counter-Insurgency at the 2017 Oregon Eclipse Festival. Issue 4 (18th May 2020) - Schwartz, Scott W.; Neumann, Matthias; Rehwinkel, Catherine Grace
Abstract: This article examines several aspects of knowledge production among practitioners of 21st century capitalism, critiquing the motivations, funding, methods, and dissemination of today's politically and economically dominant epistemology. We document a methodological experiment undertaken during the Oregon Eclipse Festival—a week-long event coinciding with the solar eclipse that crossed the United States on August 21, 2017. As commissioned participants in the festival's Art & Science exhibit, we designed an interactive archeological excavation that sought to produce material evidence corroborating the (un)reality of UFO activity in Oregon. From this performance, we highlight four insights into the relationship between science, evidence, and responsibility.